Opinion 2418: Chilicola vicugna Toro & Moldenke, 1979 (Insecta, Hymenoptera, Colletidae): neotype not designated - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has declined to use its plenary power to set aside the existing holotype of Chilicola vicugna Toro & Moldenke, 1979 and designate a neotype.